2015
DOI: 10.1186/s12990-015-0060-z
|View full text |Cite
|
Sign up to set email alerts
|

Limited Changes in Spinal Lamina I Dorsal Horn Neurons following the Cytotoxic Ablation of Non-Peptidergic C-Fibers

Abstract: BackgroundNon-peptidergic nociceptive neurons are a sub-population of small diameter primary sensory neurons that comprise approximately 50 % of the C fiber population. Together with the peptidergic sub-population, they transmit nociceptive information from the periphery to the superficial dorsal horn of the spinal cord. Despite the numerous studies investigating the role of the non-peptidergic primary afferents, their role in normal nociception and in pain remains poorly understood. Our lab has previously dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…These observations raise the interesting possibility that cold-selective SPB neurons express Gria1, rather than Gria4, thereby enabling distinct types of synaptic plasticity. Previous studies have also suggested that coldselective (albeit random) lamina I neurons in cat are pyramidal [24], and lamina I pyramidal neurons have been shown to be negative for Tacr1-immunoreactivity in rat and monkey [2,43,44,54,55]. However, the idea that cold output neurons are pyramidal remains controversial since others have suggested that there is no relation between morphology and the expression of Tacr1 in rat lamina I projection neurons [47], and most pyramidal lamina I projection neurons expressed Fos after noxious stimuli [51,52].…”
Section: Discussionmentioning
confidence: 92%
“…These observations raise the interesting possibility that cold-selective SPB neurons express Gria1, rather than Gria4, thereby enabling distinct types of synaptic plasticity. Previous studies have also suggested that coldselective (albeit random) lamina I neurons in cat are pyramidal [24], and lamina I pyramidal neurons have been shown to be negative for Tacr1-immunoreactivity in rat and monkey [2,43,44,54,55]. However, the idea that cold output neurons are pyramidal remains controversial since others have suggested that there is no relation between morphology and the expression of Tacr1 in rat lamina I projection neurons [47], and most pyramidal lamina I projection neurons expressed Fos after noxious stimuli [51,52].…”
Section: Discussionmentioning
confidence: 92%
“…AP2α2 is preferentially expressed in CGRP containing DRG neurons. Previous immunological labeling of AP2α2 in the superficial lamina of the rodent dorsal horn suggested a putative differential expression of AP2α2 in nociceptors 3,[17][18][19] . In order to resolve this, we probed mDRG neurons with antibodies against AP2α2 20 , CGRP, and an Alexa fluor-conjugated IB4.…”
Section: Resultsmentioning
confidence: 98%
“…It was shown that elimination of these neurons by injection of IB4-saporin decreased sensitivity to noxious stimuli [ 72 ] and duration of mechanical hyperalgesia [ 73 ], however, quite unexpectedly this suppression of pain response was compensated at later stages and nociceptive threshold recovered [ 72 ]. Later on, it was shown that this compensation of IB4-saporin-induced loss of nociceptive fibers includes an increase in the surface expression of NK1 receptors in the subpopulation of spinal cord neurons that already expressed NK1 receptors ( Figure 2 B) [ 74 ]. Importantly, using this saporin-based toxin it was shown that GDNF is one of endogenous mediators that can activate IB4-binding nociceptors [ 75 ].…”
Section: Saporin Conjugates As a Tool For Experimental Research Mmentioning
confidence: 99%